Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Dan Minat Belajar Matematika Siswa SMK - Amalia Retno Wulandari Siregar; Nurdalilah Nurdalilah; Desniarti Desniarti; Wilda Hasanah; Cindy Amelia Sitorus (Journal on Education, 2024)
The primary objective of this study is to ascertain the degree to which the implementation of the Problem Based Learning methodology can enhance students' interest in statistics content and mathematics learning outcomes. This investigation is a two-round classroom action research project. The study sample comprised 34 pupils enrolled in class X MPLB 5 at SMK Negeri 7 Medan. The process of gathering data was conducted via observation, questionnaires, and assessments. During the data collection phase, both teacher actions pertaining to the management of learning activities and student engagement in problem-based learning activities are assessed. Questionnaires are employed to determine the degree of interest that students have in mathematics courses. Subsequently, learning outcomes assessments are implemented to determine the degree to which pupils have comprehended the material. Based on the examination of research outcomes, one may deduce that the implementation of the Problem Based Learning pedagogical approach has resulted in enhanced scholastic performance and heightened student engagement with mathematics, particularly with regard to the domain of statistics. The observed performance increase is evident in the report of progress, which indicates a rise from 65% in the pre-cycle to 70% in cycle I, and subsequently to 95% in cycle II. The survey responses indicate that the proportion of students who are enthusiastic about acquiring knowledge in the field of mathematics rises as they progress from the pre-cycle stage to cycles I and II. More precisely, the proportion of pupils classified as "good" rose from 61.53% in the pre-cycle phase to 73.72 % in cycle I, and subsequently climbed to 87.73 percent in cycle II. The results of student learning assessments also demonstrate an upward trend. The proportion of accurate responses was 65.73% in the pre-cycle phase, 71.17% in cycle I, and 85 % in cycle II. Therefore, it can be inferred that the Problem Based Learning instructional strategy possesses the capacity to enhance students' scholastic performance and cultivate a passion for the study of mathematics